QTL Map of Early- and Late-Stage Perennial Regrowth in Zea diploperennis - Swentowsky, Kyle W.; Bell, Harrison S.; Wills, David M.; Dawe, R. Kelly (Frontiers in Plant Science, 2021)
Numerous climate change threats will necessitate a shift towards more sustainable agricultural practices during the 21st century. Conversion of annual crops to perennials that are capable of regrowing over multiple yearly growth cycles could help to facilitate this transition. Perennials can capture greater amounts of carbon and access more water and soil nutrients compared to annuals. In principle it should be possible to identify genes that confer perenniality from wild relatives and transfer them into existing breeding lines to create novel perennial crops. Two major loci controlling perennial regrowth in the maize relative Zea diploperennis were previously mapped to chromosome 2 (reg1) and chromosome 7 (reg2). Here we extend this work by mapping perennial regrowth in segregating populations involving Z. diploperennis and the maize inbreds P39 and HP301 using QTL-seq and linkage mapping approaches. The results confirmed the existence of a major perennial regrowth QTL on chromosome 2 (reg1). Although we did not observe the reg2 QTL in these populations, we discovered a third QTL on chromosome 8 which we named regrowth3 (reg3). The reg3 locus exerts its strongest effect late in the regrowth cycle. Neither reg1 nor reg3 overlap with tiller number QTL scored in the same population, suggesting these loci specifically affect perennial regrowth and not tillering. Our data, along with prior work, indicate that perennial regrowth in maize is conferred by a few major QTL.